EFEKTIVITAS MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATA PELAJARAN PAI DAN BUDI PEKERTI - Polem, Muhammad; Ningsih, Nur Wahyu; Azizah, Nurul; Ruswandi, Uus; Tarsono, Tarsono (Edukasi: Jurnal Pendidikan, 2023)
This research aimed to determine the effectiveness of the inquiry learning model in improving students' cognitive learning outcomes in PAI and Budi Pekerti subjects. The research method used is a quantitative approach with a pre-experimental design type one group pretest-posttest (single group pretest-final test). The population consisted of all students in class VIII, while the sample was taken from class VIII C using a non-probability sampling technique. Data collection techniques include observation, interviews, and test techniques in the form of multiple-choice questions. Analysis of Data used the Paired Sample t-test statistical test, SPSS version 26 software. The results showed a Z value of -4.743 with a p-value (Asymp. Sig. 2 tailed) of 0.000 which is smaller than the significance value of 0.05 with the decision H0 was rejected so that there was a notable distinction in the cognitive learning results of students in Islamic Education and Characteristics subjects between before and after the applying the inquiry-based learning model. Thus, the inquiry learning model applied in Islamic Education and Characteristics subjects effectively improves the outcomes of cognitive learning students.